A qualitative study on menopause described from the man's perspective - (:unkn) unknown (PAKISTAN MEDICAL ASSOC, 2014)
Objective: To look at menopause from men's point of view and to provide a better understanding of this phase to improve the care delivered to menopausal women. Methods: The study was conducted at the health centre of a single district of Istanbul, from April 2013 to June 2013, which serves as the research and training area of the Marmara University and which receives migrations from mainly southern and eastern regions of Turkey. The study sample included 33 married men. Qualitative in-depth interviews were performed individually and main themes were noted down for analysis. Results: The age range of the study population was 40-77 years. The subjects lacked basic knowledge about both menstruation and menopause. Most of the participants defined menopause as loss of fecundity, increased weight, and loss of beauty. The most important concern voiced was men's own sexual life. None of the men had heard about treatment modalities available for menopause. Conclusion: Interventions are needed to increase men's awareness regarding menopause in order to help these men to be able to better support their spouses so that they can both have a smooth transition into postmenopausal years.
Keywords: Men; Menopause; Qualitative; Turkish; Perceptions; In-depth; WOMEN